ANALYSIS OF SELECTION OF JOINT TRAINING AREA’S TO INTEGRATE THE ABILITIES OF INDONESIAN SPECIAL FORCES - Taufik Ramdhan; Joko Purnomo; Adi Bandono (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2021)
The Indonesian National Armed Force has special forces that come from the three divisions, the Army, Navy, and Air Force. Even though they are both elite troops, the three dimensions have different combat specialties. A joint scale training is needed to integrate and increase the professionalism of these three special forces dimensions. Therefore, to optimize the ability of these special forces, a training area that is really suitable is needed so that this joint training can run well. This study aims to provide an analytical framework related to the selection of a joint training ground for the TNI special forces. 1The method used is the Simple Additive Weight (SAW) method. This method is known as the weighted addition method. 1The basic concept 1of the SAW method is to find the weighted sum of the performance ratings for each alternative on all attributes Based on this research, it is concluded that from the available alternatives, the best priority for training sites is Sangatta with a weight value of 0.781, then Natuna with a weight value of 0.768 then Saumlaki with a weight of 0.620. Key Words : Special Force, Joint Training, SAW